Enhancing pre-service mathematics teachers understanding of sampling distributions with conceptual change texts - Zeynep Medine Özmen; Bülent Güven (Journal of Pedagogical Research, 2022)
The present study aimed to remediate pre-service teachers' misconceptions about sampling distributions and to develop their conceptual understanding through the use of conceptual change texts (CCTs). The participants consisted of 84 pre-service teachers. To determine the pre-service teachers' conceptual understanding of sampling distributions, an achievement test was utilized. Five conceptual change texts were prepared. In this study, the number of correct responses of pre-service teachers increased from pre-test to post-test and delayed test. This increase was statistically significant in favor of the post-test and delayed test. The results demonstrated that, due to the knowledge gained from the CCTs, the pre-service teachers improved their conceptual understanding about sampling distributions. Moreover, this study represents an important effort to integrate CCTs in mathematics and statistics education.